Which is the best communication strategy, based on anti-tobacco ads, to impress teenagers? A multicenter cross-sectional study - Mannocci, A.; D'Egidio, V.; Gualano, M. R.; Guerra, F.; Mascagna, F.; De Marco, Y.; Boccia, G.; Giordano, D.; Firenze, A.; Siliquini, R.; La Torre, G. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Well-planned mass-media campaigns can increase health literacy and raise awareness about the consequences of tobacco use. This study aims to evaluate the emotions and opinions of adolescents about several anti-tobacco spots delivered by the mass media over the world. Study design. Cross-sectional study.Methods. The study was conducted in Italy in 2016-2017 among students aged 13-17 years. Students expressed their emotions and opinions about seven anti-tobacco spots from all over the world on different topics and styles. Results. 499 students attended. The video “Sponge” was found to be the most impressive (30.2%) and what they would have chosen if they had been responsible for campaign launched by the Minister of Health (40.5%). The “Icons” spot ranged second, with 19.2% and 17.4%, respectively.Conclusions. In summary, this study showed that the communication strategies most effective, according to the students interviewed, are those that give clear messages with a scientific profile or that discover the false stereotypes, as in the video “Icons”.However, further research is needed to investigate the effectiveness of TV campaigns against smoking, in terms of habits and knowledge in young people.